Chemical constituents of Psidium guajava leaves and their antibacterial activity. (June 2021) - Huang, Jiwu; Li, Chuangjun; Ma, Jie; Xu, Kailing; Chen, Xinyi; Jiang, Jiandong; Zhang, Dongming
Abstract: Seven undescribed compounds, namely (+)-psiflavanone A, (−)-psiflavanone A, (+)-psiflavanone B, (−)-psiflavanone B, (+)-psiketide, (−)-psiketide, and psidinone, were isolated and chirally separated from the 95%-ethanol extract of Psidium guajava leaves. (+)/(−)-Psiflavanone A and (+)/(−)-psiflavanone B are two pairs of rare enantiomeric C -benzoylated flavanones isolated from the title plant for the first time. (+)/(−)-Psiketide are a pair of enantiomeric aromatic polyketides, and psidinone is the first example of a C18 phenanthrenediquinone with an angle-type 6/6/6 tricyclic skeleton. Their structures were identified by extensive analysis of HRESIMS, UV, IR, NMR, and calculated electronic circular dichroism (ECD) data. Particularly, the structures of (+)-psiflavanone A, (−)-psiflavanone A, (+)-psiflavanone B, and psidinone were further confirmed by X-ray diffraction. Psidinone exhibited antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, and Mycobacterium Smegmatis mc 2 155, with minimum inhibitory concentrations (MICs) of 16, 8, and 0.5 μ M, respectively. These results not only highlight the chemical diversity and biological activity of P. guajava but are also expected to pave way for its further expansion to other applications in future. Graphical abstract: Seven undescribed compounds were isolated from Psidium guajava leaves and their antibacterial activity were evaluated. Image 1 Highlights: Seven undescribed compounds were isolated from Psidium guajava leaves. Rare enantiomeric C -benzoylated flavanones were isolated from this plant for the first time. Psidinone was the first example of C18 phenanthrenediquinone with an angle-type 6/6/6 tricyclic skeleton. Psidinone revealed antibacterial activity against Mycobacterium Smegmatis mc 2 155 with MIC value of 0.5 μ M.